2013
DOI: 10.4166/kjg.2013.61.5.265
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Necrosis of the Cecum: A Single Center Experience

Abstract: Isolated cecal necrosis should be considered in elderly patients with chronic diseases presenting with sudden right lower quadrant pains in the differential diagnosis. Isolated cecal necrosis may have a bad prognosis since it is seen in elderly patients with accompanying problems. Therefore, early diagnosis and immediate surgical management if necessary is important to reduce the risk of morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…Ischemic colitis, especially left colon, is the most common form of gastrointestinal ischemia [2]. Therefore, ischemic colitis involving the right colon is an infrequent occurrence while ischemic colitis involving only the cecum is extremely rare, as shown by Scharff et al [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic colitis, especially left colon, is the most common form of gastrointestinal ischemia [2]. Therefore, ischemic colitis involving the right colon is an infrequent occurrence while ischemic colitis involving only the cecum is extremely rare, as shown by Scharff et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…It mostly develops in relation to atherosclerosis and low blood flow of colon arteries [2]. Isolated cecal necrosis is a rare form of acute colonic ischemia and a rare cause of surgical abdomen [3].…”
Section: Introductionmentioning
confidence: 99%
“…In 26% of cases, histopathology showed nonspecific changes, and the patients were asymptomatic on follow up without any treatment . The various causes of ICT are listed in Table …”
Section: Causes Of Ictmentioning
confidence: 99%
“…It usually presents with abdominal pain, diarrhea, and bleeding per rectum. Ischemic colitis should always be considered whenever any patient with predisposing factors presents with acute right iliac fossa pain …”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Acute colonic ischemia is usually seen in the elderly population as a result of atherosclerosis and low blood flow which can cause colitis and rectal bleeding. Acute nonocclusive ischemia of the colon manifested as isolated cecal necrosis is a rare condition which mostly occurs in patients with chronic renal failure or heart failure and 9% to 20% of deaths in hemodialysis dependent patients are attributable to nonocclusive mesenteric ischemia or bowel infarction (1)(2)(3) . Although there is not a consensus on gender and the age of the pati- ents under chronic dialysis presenting with nonocclusive mesenteric ischemia, Yaacov Ori et al (4) reported the mean age of the patients as 70.8±1.8 years, and the male:female ratio of 7:13 in these patients.…”
Section: Introductionmentioning
confidence: 99%